Language learning in a partially English-taught teacher education programme: language gains and student perceptions - Barrios-Espinosa, María Elvira; López-Gutiérrez, Aurora (Taylor & Francis, 2021)
This paper reports on a study aimed to investigate students’ development in English proficiency over a four-year partially English-taught programme that did not integrate any explicit language learning goals. Additionally, the study investigated their perceptions concerning language gains and experiences in the programme. Both quantitative and qualitative research methods were employed. Paired-sampled t-tests indicated statistically significant differences from pretest to posttest for listening but not for grammar. Repeated measures ANOVA determined that the least proficient (B1) students obtained the highest language gains over the 4-year period, particularly in listening. In contrast, advanced (C1) students performed worse in the listening and grammar posttests than in the pretests. Further findings indicated that the students perceived a positive impact on their English competence. No significant differences were found across self-rated proficiency groups regarding their perceptions of language improvement as a result of participating in the programme. The study also found that the higher the students’ proficiency in the language, the less satisfied they were with the programme. In the focus group interviews, the students attributed their language improvement to being exposed to English and having to produce output, mainly in oral presentations and written tasks, and demanded English language instruction within the curriculum.
Keywords: Inglés - Estudio y enseñanza; Enseñanza superior; Enseñanza bilingüe; English Medium Instruction; English proficiency; Higher education; Bilingual programme; Student perceptions